Smart antennas in wireless communications base-station diversity and handset beamforming. - Dietrich, Carl B. Jr (IEEE Antennas & propagation magazine.)
We review diversity and smart antenna research applied to both base-stations and terminals. To illustrate the performance gains possible, the paper describes research being conducted by the Smart Antenna Group at Virginia Tech, in both smart base-stations and smart handheld terminals.